2021
DOI: 10.1007/s00383-021-05016-8
|View full text |Cite
|
Sign up to set email alerts
|

Surgeon, patient, and caregiver perspective of pediatric surgical telemedicine in the COVID-19 pandemic era

Abstract: Purpose Adoption of telemedicine (TME) in surgical specialties, prior to the COVID-19 pandemic, has previously been slow. The purpose of this prospective, observational, single institution study is to evaluate surgeon and caregiver perspectives of TMEs during the pandemic. Methods Surveys were distributed to surgical faculty regarding perceptions of TME early during the pandemic and 2 months later. Caregivers (or patients > 18 years old) were asked after each TME to com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…To our knowledge, Diaz-Miron et al is the only other study published to show a statistically significant trend of more seasoned providers having less enjoyable experiences utilizing telemedicine during COVID-19. Specifically, they found that older surgeons in their population had similar satisfaction at the onset of COVID-19, but at a two-month follow-up, a significant downward trend in satisfaction was noted in their older surgeon base compared to younger surgeons [ 23 ]. Also, Aliberti et al ran a noteworthy qualitative study where they looked at primary care providers' perceptions of patients 65 years or older using telemedicine during COVID-19.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, Diaz-Miron et al is the only other study published to show a statistically significant trend of more seasoned providers having less enjoyable experiences utilizing telemedicine during COVID-19. Specifically, they found that older surgeons in their population had similar satisfaction at the onset of COVID-19, but at a two-month follow-up, a significant downward trend in satisfaction was noted in their older surgeon base compared to younger surgeons [ 23 ]. Also, Aliberti et al ran a noteworthy qualitative study where they looked at primary care providers' perceptions of patients 65 years or older using telemedicine during COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…23. For perceptions of overall experiences, cardiologists reported a mean score of 4.25, and other providers reported a mean score of 3.83, U = 121.00, z = -1.333, p = 0.26.…”
mentioning
confidence: 99%
“…A survey of caregivers who participated in at least one pediatric surgery telemedicine appointment during the COVID-19 pandemic found that 79% thought telemedicine was equivalent to, if not better, than an in-person visit [ 6 ]. A second survey study reported that the majority of families received excellent pediatric surgical care (76%) and would choose telemedicine again in the future (57%).…”
Section: Manuscript Bodymentioning
confidence: 99%
“…Following the COVID-19 pandemic, telemedicine has also provided safety benefits by limiting opportunities for viral exposure for both patients and healthcare workers. Despite the benefits and dramatic increase in utilization of telemedicine for the past 15 years in primary care and behavioral health, telemedicine utilization in pediatric urology in the United States was uncommonly reported prior to the COVID-19 era (7)(8)(9)(10)(11). A variety of potential medical, reimbursement and regulatory, and ethical barriers have been proposed to contribute to this lack of utilization (2,8,12).…”
Section: Introductionmentioning
confidence: 99%
“…A variety of potential medical, reimbursement and regulatory, and ethical barriers have been proposed to contribute to this lack of utilization (2,8,12). But, in the United States, the driving force for the rapid and widespread utilization of telemedicine-almost overnight-seemed to be contingent on keeping practices financially viable, i.e., 1) the sudden inability to see patients in-person due to stay-at-home orders during the onset of the COVID-19 pandemic and 2) the subsequent financial incentives and relaxed regulations that were provided by the federal government (7,9). Though there has been a gradual decline in telemedicine utilization among pediatric urologists in the United States since mid-2020 due to the lifting of stay-at-home restrictions and the re-opening of clinic capacities, utilization may still be greater than pre-pandemic levels, as is evidenced at one institution (7), and, if the financial and regulatory incentives for telemedicine remain intact, it is assumed telemedicine will remain a critical healthcare delivery modality in the United States.…”
Section: Introductionmentioning
confidence: 99%